Outcomes of catheter ablation of ventricular tachycardia in non-ischemic idiopathic dilated cardiomyopathy: A systematic review and meta-analysis - Ammar, Ahmed; Sharief, Mohamed; Abouelmagd, Khaled; Riad, Omar; Ibrahim, Mokhtar (Frontiers in Cardiovascular Medicine, 2022)
Objective To perform a systematic review and meta-analysis of available trials regarding the outcomes of ventricular tachycardia (VT) ablation in patients with non-ischemic dilated cardiomyopathy (NIDCM). Methods A comprehensive database search of large four electronic databases, including PubMed, Cochrane, Scopus, and Institute for Scientific Information network meta-analysis, identified five studies enrolling 666 patients for patients with idiopathic dilated cardiomyopathy (IDCM) underwent catheter ablation (CA) for VT. The short-term outcomes assessed included procedural success, VT non-inducibility and procedural complications, whereas the long-term outcomes assessed included VT recurrence, heart transplantation, antiarrhythmic drugs (AAD) use after ablation and death. Results A total of 5 observational studies reported outcomes in 666 patients with NIDCM undergoing VT CA. The complete procedural success was moderately high; 65.5% of the patients (95% CI 0.402- 0.857, p < 0.001) and the procedural complications occurred in 5.8% of the patients (95% CI 0.040–0.076, P = 0.685). Epicardial mapping and ablation were performed among 61.5% and 37% of patients with NIDCM respectively. During a follow up period of 12 to 45 months, there were VT recurrence in 34.2% of the patients (95% CI 0.301–0.465, p < 0.080), death in 20.2% of the patients (95% CI 0.059–0.283, p < 0.017) and heart transplantation in 12.9% of the patients (95% CI −0.026–0.245, P < 0.012). Conclusion Ventricular tachycardia CA is effective and safe approach for management of patients with NIDCM with the epicardial approach to be considered as initial strategy especially in presence of ECG and CMR findings suggestive of epicardial substrate. A multicenter randomized trial is crucial to look at the short- and long-term outcomes of VT ablation in NIDCM especially with the advances in mapping and ablation techniques and predictors of success.